Esthetic rehabilitation with ultra-thin ceramic veneers and direct mock-up in the treatment of dental erosion - Case Report - Fernando Grandon; Natalia Marcus; Maria Muster (Universidad de Concepción., 2018)
Dental erosion is a high prevalence condition characterized by the loss of dental substance due to chemical agents. It can also be associated with physical wear, affecting function and aesthetics. Ceramic veneers can provide effective solutions to patients affected by erosive disorders, by means of an indirect approach and minimal intervention. Recent advances in cementation techniques and ceramic materials have allowed their use in reduced thicknesses, known as "dental contact lenses" or "ultra-thin veneers". They contribute significantly to the preservation of the dental structures, having excellent mechanical properties and providing satisfactory aesthetic solutions. Their manufacture requires rigorous planning and the use of three-dimensional models or mock ups in order to preview the final outcome. Case: The aim of this report is to communicate the use of this technique for the treatment and successful 12-months follow-up of a patient affected by dental erosion of the maxillary central incisors. Special interest was placed on direct mock-up, which is a simple technique not requiring laboratory steps. Luting of the lithium disilicate veneers was carried out with a light-curing resin cement and try-in pastes, yielding a very satisfactory result. Conclusion: Diagnosis and early treatment of this disorder allows the application of conservative techniques, such as ultra-thin veneers, which are seen as a promising alternative treatment to full coverage restorations and traditional ceramic veneers.